2020
DOI: 10.1016/j.bjps.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of early compression of free flaps following lower limb reconstruction: A systematic review

Abstract: Introduction: Early postoperative compression of free flaps for lower limb reconstruction remains controversial. It may reduce venous congestion and promote resolution of oedema. However, concerns remain regarding inadvertent pedicle compression, which may lead to flap failure. The aim of this systematic review was to determine the safety and effectiveness of this intervention. Methods: A systematic review was designed in compliance with PRISMA. MEDLINE and EMBASE databases were searched. Parallel screening, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…First, after free flap reconstruction, patients undergo a period of extensive immobilization, which may facilitate the development of a prothrombotic state, particularly after surgery 27 . In addition, after these reconstructions, the vascular pedicle or anastomosis of the flap may be compromised by a number of intrinsic and extrinsic factors 28 . Among the potential internal factors, compression may be caused by postoperative edema, metal implants, and bony prominences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, after free flap reconstruction, patients undergo a period of extensive immobilization, which may facilitate the development of a prothrombotic state, particularly after surgery 27 . In addition, after these reconstructions, the vascular pedicle or anastomosis of the flap may be compromised by a number of intrinsic and extrinsic factors 28 . Among the potential internal factors, compression may be caused by postoperative edema, metal implants, and bony prominences.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, after these reconstructions, the vascular pedicle or anastomosis of the flap may be compromised by a number of intrinsic and extrinsic factors. 28 Among the potential internal factors, compression may be caused by postoperative edema, metal implants, and bony prominences. Externally, vascular pedicles and the integrity of the anastomosis may be jeopardized by circumferential dressings, compressive splints/wraps, or compression on surrounding objects in physical space (ie, hospital bed, pillows, leg elevating structures).…”
Section: Timing Of Reoperation After Le Free Flap Reconstructionmentioning
confidence: 99%
“…In a study involving a total of 38 patients with forearm hematoma following coronary intervention, Berner et al compared the results of injecting dehydrating agents in the hand dorsal vein between the affected and the non-affected sides. They found that injection in the hand dorsal vein of the affected side could relieve pain faster, promote better edema regression, and reduce the occurrence of tension blisters ( 15 ). Jonker et al compared the curative effects of tension hematoma on the anterior wall following coronary intervention of hand compression, elastic bandage compression alone, and bandage compression combined with dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…With advances in the field of microvascular surgery, success rates of FTT have continued to increase, estimated to be more than 95% and as high as 98% to 99% in some case series. [6][7][8][9][10] The most common causes of flap failure are hematoma and/or thrombus formation, both of which can hinder subsequent revascularization attempts and may ultimately compromise flap salvageability. [11][12][13] Because of this, the surgical team must strike a careful balance to achieve an arterial pressure that is conducive to adequate tissue perfusion but not so high that it hinders adequate homostasis.…”
mentioning
confidence: 99%
“…Free tissue transfer (FTT) is a reconstructive modality that allows for limb salvage in patients who might otherwise be subject to amputation. With advances in the field of microvascular surgery, success rates of FTT have continued to increase, estimated to be more than 95% and as high as 98% to 99% in some case series 6–10 . The most common causes of flap failure are hematoma and/or thrombus formation, both of which can hinder subsequent revascularization attempts and may ultimately compromise flap salvageability 11–13 .…”
mentioning
confidence: 99%